Correction of Biapical Radial Deformities by Use of Bi‐Level Hinged Circular External Fixation and Distraction Osteogenesis in 13 Dogs. Issue 3 (10th January 2014) - Kwan, Toni W.; Marcellin‐Little, Denis J.; Harrysson, Ola L.A.
<x xml:space="preserve">Abstract</x> Objectives To describe clinical, radiographic, and computed tomographic (CT) assessment of biapical deformities of the radius in dogs and evaluate the effectiveness of their management by use of bilevel hinged circular external fixation frames. Study design Prospective, non‐randomized cohort study. Animals Dogs (N = 26: 13 with 14 limbs operated, 13 controls). Methods CT scans of the forelimbs were performed and CT‐based polymer replicas prepared. Rotation within the elbow joint, varus of the proximal portion of the radius, radial torsion, valgus of the distal portion of the radius, procurvatum, and rotation within the carpal joint were measured on radiographs, on polymer replicas, and on CT scans. Bilevel hinged circular external fixation frames were assembled on polymer replicas and identical frames were placed on dogs. Torsion was corrected acutely and angulation was corrected progressively. Functional outcome was assessed subjectively. Results Buckling was present preoperatively in operated limbs. Mean (±SD) varus of the proximal portion of the radius was 36 ± 8°, valgus of the distal portion of the radius was 32 ± 5°, external radial torsion was 35 ± 6°, procurvatum was 41 ± 10°, and medial translation was 44 ± 11 mm. Treatment duration was 80 ± 24 days. Buckling was not observed after surgery. Lameness scores improved in all dogs (P < .001). Conclusions The forelimbs of dogs with severe biapical radial deformities buckle and have increased radial head rotation and radial torsion. Biapical radial deformities can be managed with proximal and distal radial osteotomies and bilevel hinged circular external fixation.